Effects of Ramadan intermittent fasting and pattern of nutrients intake on BMI and MUAC of a population consisting of Indian Muslims. Issue 8 (14th September 2021) - Das, Aindrila; Hasmat, Nafisa; Kumar Ghosh, Samir; Sahu, Subhashis
ABSTRACT: 'Ramadan' is observed by the Muslims around the world, out of their religious belief, as a period when they fast all day and break fasting only after sun set. The Ramadan fasting, which can be viewed as alternate fasting owing to the nature of food intake during this time, stretches for 28 days. The food intake prior to sun rise is known as 'sahour' and that after sunset is called 'iftar'. In view of intermittent fasting, the present work aims to study the food intake pattern among children, adults and elderly persons before and after Ramadan in the eastern part of India to evaluate the effect of Ramadan fasting on body weight and BMI, if any. Anthropometric measurements, body weight, height, BMI, Mid Upper Arm Circumference (MUAC) and Nutritional Survey were done before and after Ramadan fasting. All three age groups showed increase in body weight and BMI after one month of Ramadan fasting compared to the values of pre Ramadan control. Excess intake of fat, sugar and energy along with a sedentary work routine are the main factors identified as contributors toward such increase. The study also points out socio-economic status as an important determinant.